Prenatal exposure to bisphenol A and/or diethylhexyl phthalate alters stress responses in rat offspring in a sex- and dose-dependent manner - Kaimal, Amrita; Hooversmith, Jessica M.; Cherry, Ariana D.; Garrity, Jillian T.; Al Mansi, Maryam H.; Martin, Nicholas M.; Buechter, Hannah; Holmes, Philip V.; MohanKumar, Puliyur S.; MohanKumar, Sheba M. J. (Frontiers in Toxicology, 2023)
Background: Prenatal exposures to endocrine disrupting chemicals (EDCs) are correlated with adverse behavioral outcomes, but the effects of combinations of these chemicals are unclear. The aim of this study was to determine the dose-dependent effects of prenatal exposure to EDCs on male and female behavior. Methods: Pregnant Sprague-Dawley rats were orally dosed with vehicle, bisphenol A (BPA) (5 μg/kg body weight (BW)/day), low-dose (LD) diethylhexyl phthalate (DEHP) (5 μg/kg BW/day), high-dose (HD) DEHP (7.5 mg/kg BW/day), a combination of BPA and LD-DEHP (B + D (LD)), or a combination of BPA and HD-DEHP (B + D (HD)) on gestational days 6–21. Adult offspring were subjected to the Open Field Test (OFT), Elevated Plus Maze (EPM), and Shock Probe Defensive Burying test (SPDB) in adulthood. Body, adrenal gland, and pituitary gland weights were collected at sacrifice. Corticosterone (CORT) was measured in the serum. Results: Female EDC-exposed offspring showed anxiolytic effects in the OFT, while male offspring were unaffected. DEHP (HD) male offspring demonstrated a feminization of behavior in the EPM. Most EDC-exposed male offspring buried less in the SPDB, while their female counterparts showed reduced shock reactivity, indicating sex-specific maladaptive alterations in defensive behaviors. Additionally, DEHP (LD) males and females and B + D (LD) females displayed increased immobility in this test. DEHP (LD) alone and in combination with BPA led to lower adrenal gland weights, but only in male offspring. Finally, females treated with a mixture of B + D (HD) had elevated CORT levels. Conclusion: Prenatal exposure to BPA, DEHP, or a mixture of the two, affects behavior, CORT levels, and adrenal gland weights in a sex- and dose-dependent manner.